THEORETICAL VIEWS ON MICROCREDIT AND TRENDS IN THEIR DEVELOPMENT - Dusbayev Utkir Khidirovich (American Journals, 2025)
The article examines theoretical views on microcrediting and their development trends, practice and specific aspects of microcrediting. Based on the results of the study, the positive and negative aspects of microcrediting were identified, and appropriate developments were formed for its application in credit organizations in Uzbekistan. Also, the article analyzes the researches, scientific works and economic literature of foreign and local scientists on the topic.